Combining Motivating Strategies with Design Concepts for Mobile Apps to Increase Usability for the Elderly and Alzheimer Patients - Eichhorn, Christian; Plecher, David A.; Lurz, Martin; Leipold, Nadja; Böhm, Markus; Krcmar, Helmut; Ott, Angela; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
This work focuses on design concepts, including the goal to motivate interaction with mobile applications for the target group elderly people and with an extended set of guidelines for Alzheimer patients. At the outset, understanding the symptoms of Alzheimer’s disease is necessary when focusing on usability issues during interaction with touchscreen-based devices. Improving health via the use of mobile devices is a game changer in many areas. However, an urgent need exists for a fitting theory-based approach, which is missing in many applications, to facilitate the countering of threats such as diseases, age-related decline and situational factors. When assessing various projects, only focusing on how to utilize mobile devices to improve the life quality of the elderly is not adequate. An even more critical aspect is how to motivate them to actually use mobile devices, which is inevitable. Therefore, based on our guidance required in the development process, it must include intrinsic and extrinsic motivational strategies to target different user types for mobile applications. With that in mind, we review design strategies when developing for the elderly. Additionally, we offer useful recommendations to form a set of Design Guidelines that are structured to address the three major categories of age-related decline: Cognitive, Perceptual and Motor Abilities. We conclude with an innovative view on application development by introducing Enabling Applications, which focus on elderly people, Alzheimer patients and their caregivers alike.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Aging Society; Alzheimer’s Disease; Design; Elderly; Gamification; Gerontechnology; Guidelines; HCI; Motivation; Nursing Home; Serious Games